First offshore bond issuances and firm valuation - Dimic, Nebojsa; Orlov, Vitaly; Piljak, Vanja (Elsevier, 2022)
Does the first offshore bond initial public offering (BIPO) affect firm valuation? By using a sample of US firms we document the dynamics of the firm valuation in response to initial offshore bond issuance. We find that offshore BIPOs have a positive short-term effect on US firms' valuations. The effect varies in firm characteristics, timing, and the location of the issue. Positive valuation effect is further confirmed by using difference-in-differences analysis approach, where offshore bond issuers are compared with their domestic counterparts. Additionally, firms with a strong need for external funds and growth prospects accelerate their offshore public debt market entry.
Keywords: Bond IPO; Debt structure; International bond market; Tobin's q; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|